2023
DOI: 10.1108/jhtt-05-2021-0149
|View full text |Cite
|
Sign up to set email alerts
|

Resource-based view theory perspective of information technology capabilities on organizational performance in hospitality firms: a time-lagged investigation

Khalid Mehmood,
Adil Zia,
Haseena Bader Alkatheeri
et al.

Abstract: Purpose This study aims to investigate the link between information technology capabilities (ITC) and organizational performance (OP) in the hospitality industry by focusing on the indirect effect of sustainability practices, service innovation (SINO), service improvement (SIMP) and the moderating role of top management support (TMS). Design/methodology/approach Time-lagged survey data from 488 hotel managers in the United Arab Emirates was used in this study to examine the hypotheses by the PROCESS Macro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The principal axis factoring method revealed that the first factor accounted for only 25.83% of the variance, indicating a minimal impact of CMB, as corroborated by prior studies. [99][100][101][102] Furthermore, the sample adequacy measure, with a value of 0.917, surpassed the acceptable threshold of 0.80, confirming the adequacy of the sample size for this study.…”
Section: Common Methods Variancesupporting
confidence: 70%
“…The principal axis factoring method revealed that the first factor accounted for only 25.83% of the variance, indicating a minimal impact of CMB, as corroborated by prior studies. [99][100][101][102] Furthermore, the sample adequacy measure, with a value of 0.917, surpassed the acceptable threshold of 0.80, confirming the adequacy of the sample size for this study.…”
Section: Common Methods Variancesupporting
confidence: 70%
“…This approach, increasingly prevalent in contemporary research, facilitates multiple survey administrations within a specific study framework (Mehmood, Jabeen, Rehman, et al, 2023;Shah et al, 2023). By leveraging data from diverse sources, this method effectively mitigates the risks associated with common source bias (CMB) (Alkatheeri et al, 2023;Mehmood, Zia, Alkatheeri, et al, 2023). Additionally, the time-lagged approach's inherent design, which allows for intervalbased data collection, further diminishes CMB concerns (Podsakoff et al, 2003;Mehmood, Kautish, Mangla, et al, 2024).…”
Section: Data Collectionmentioning
confidence: 99%
“…The study involved senior-level managers from each SME, who received a comprehensive briefing on the research objectives and data collection procedures. A time-lagged approach, in line with recent empirical studies (Mehmood, Zia, et al, 2023;Shah et al, 2023), was adopted to gather data at different time intervals. This approach is widely recognized in contemporary research as it permits researchers to conduct surveys for specific research objectives at multiple time intervals.…”
Section: Data Collection and Proceduresmentioning
confidence: 99%